PERRON-FROBENIUS THROREM FOR MAX ALGEBRA - (NIM: 20107071), AFRIZAL
In general this project describe the generalization of classic Perron-Frobenius Theorem to max algebra. This Project uses a description method through study literature. It is shown the proof of Perron-Frobenius Theorem In Max Algebra.